German-Russian gas relations: A special relationship in troubled waters - Aurélie Bros; Tatiana Mitrova; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2017)
In the context of the security crisis in and over Ukraine, natural gas imports from Russia have become a source of debate in Germany and the European Union. Natural gas relations with Russia are often analyzed either through the prism of commercial and market-based transactions or that of foreign policy and geopolitics. In that respect, this Research Paper takes a holistic approach and tries to analyze and define the dynamics of (geo)politics and economic/commercial logics from the beginning of the early 1970s until today. The paper provides insights into the conducting of German-Russian gas relations at the levels of infrastructure development, trade, business-to-business and commercial ties, as well as political framing. It explains the nature and texture of the gas relations, which have been subject to change over time.
Keywords: 320